(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to formulate and analyze the effectiveness of Fun Learning Strategies (SPM) in improving Qur’an reading skills in early childhood. The research method used is a literature study and comparative analysis of relevant academic works regarding innovative models and active strategies for Qur’an learning in early childhood. The results of the study conclude that an effective SPM must be an integrated framework that combines four main pillars: (1) Innovation and ICT media to attract interest and create meaningful experiences; (2) An Active Learning approach to ensure children’s active participation; (3) An individual approach and the Tahfizh method for in-depth mastery and regular practice; and (4) A reward system to maintain and strengthen motivation. The main conclusion shows that the comprehensive implementation of SPM successfully improves children’s Qur’an reading skills optimally because the learning process aligns with their natural development. This study contributes to providing a practical strategic model for teachers and PIAUD institutions.